Health information seeking behavior of parents, with children ages 0–5, from Mogpog, Marinduque, focusing on pneumonia - Mallorca, Hennessy Jane N.
Pneumonia remains as the leading cause of mortality among children under 5 years of age. Lack of knowledge to recognize the symptoms and delayed health-seeking of parents are the main reasons that increase mortality rate. Thus, seeking immediate and appropriate health information is crucial. Therefore, this study sought to understand the health information seeking behavior of parents, with children ages 5 years and below, who act as lay information mediaries. However, due to the restrictions imposed by the COVID-19 pandemic, snowball sampling was employed to recruit respondents from Mogpog, Marinduque and printed questionnaires were distributed. Results showed that personal sources were the most preferred, utilized, and regarded as the most credible and best source of health information. The respondents were the most aware (90.5%), have the highest access (77.4%), information receipt (32.1%), and use in healthcare decision-making (70.2%) of health information from barangay health centers; health information provided by doctors or physicians were most utilized (85.7%). While majority of the parents favored sources that provides up-to-date information (n=62), the least number of parents cited religious teaching (n=2) as having influenced in their choice of information source. Bivariate analysis using chi square test of independence determined the following socio-demographic characteristics as significant indicators of the frequency of use of various information sources at α=0.05: residence, age, sex, religion, and monthly family income. Two-tailed multivariate analysis using Kendall’s tau b indicated concordance among perception of credibility (p=0.000), frequency of health information use (p=0.000), and frequency of information source use (p=0.000) at α=0.01.